Biocomercio: oportunidad de desarrollo empresarial - Primo Tapia, Wilfrido de Jesús (Cuadernos de Estudios Empresariales, 2017)
In this paper, bio-commerce is presented as an opportunity for business and social development that favors the preservation of the environment. In addition, it is presented as a priority strategy to preserve it. For this, the possible genesis of the term BioTrade is explored, the commitments that the nations acquire as a consequence of the devastation of the environment, which lead to the definition of policies and strategies to encourage the exploitation and conservation of biodiversity. Finally, the most biodiverse countries are identified, highlighting the most naturally gifted and with the greatest potential to develop bio-trade. In the case of Colombia, there is an evolution of the policies related to the environment, the changes made in the matter, to the commitments made since the Rio summit and the impact it has had on the protection of the environment and the growth of Biodiversity business. To this end, documentary finds are made on the history of trade between Europe and the East during the Middle Ages. In addition, they are documented with the main historical commitments of the last century and the implications that would have in the countries less developed. In the same way, the evolution of Colombian environmental legislation has been documented historically. Finally, statistical data show the global distribution of biodiversity, highlighting the differences between the countries, and then show the potential of these and Colombia for the development of Biotrade activities.